2004
DOI: 10.1128/aem.70.9.5177-5182.2004
|View full text |Cite
|
Sign up to set email alerts
|

Copper Ions Stimulate Polyphosphate Degradation and Phosphate Efflux in Acidithiobacillus ferrooxidans

Abstract: For some bacteria and algae, it has been proposed that inorganic polyphosphates and transport of metalphosphate complexes could participate in heavy metal tolerance. To test for this possibility in Acidithiobacillus ferrooxidans, a microorganism with a high level of resistance to heavy metals, the polyphosphate levels were determined when the bacterium was grown in or shifted to the presence of a high copper concentration (100 mM). Under these conditions, cells showed a rapid decrease in polyphosphate levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
117
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 28 publications
14
117
0
2
Order By: Relevance
“…Similar stimulatory effects of Cu have also been observed for exopolyphosphatase (PPX) activity of A. ferrooxidans up to 1-2 μM Cu, where inhibition in the PXX activity occurred for Cu concentrations greater than 5 μM (Alvarez and Jerez, 2004), and up to 10 μM Cu for the archaeon Sulfolobus metallicus (Remonsellez et al, 2006). Zn was also observed to stimulate the PXX activity of A. ferrooxidans at 1-2 μM concentrations; however, this stimulation effect was only half compared to that of exposure to Cu (Alvarez and Jerez, 2004). Stimulation effect of Zn on the PXX activity was also seen for S. metallicus in the micromolar range, similarly lower than of the Cu effect (Remonsellez et al, 2006), both consistent with our observations with Arthrobacter sp.…”
Section: Exposure Of Arthrobacter Sp To Zn and Cu At 35 °Csupporting
confidence: 49%
“…Similar stimulatory effects of Cu have also been observed for exopolyphosphatase (PPX) activity of A. ferrooxidans up to 1-2 μM Cu, where inhibition in the PXX activity occurred for Cu concentrations greater than 5 μM (Alvarez and Jerez, 2004), and up to 10 μM Cu for the archaeon Sulfolobus metallicus (Remonsellez et al, 2006). Zn was also observed to stimulate the PXX activity of A. ferrooxidans at 1-2 μM concentrations; however, this stimulation effect was only half compared to that of exposure to Cu (Alvarez and Jerez, 2004). Stimulation effect of Zn on the PXX activity was also seen for S. metallicus in the micromolar range, similarly lower than of the Cu effect (Remonsellez et al, 2006), both consistent with our observations with Arthrobacter sp.…”
Section: Exposure Of Arthrobacter Sp To Zn and Cu At 35 °Csupporting
confidence: 49%
“…We have recently found that Acidithiobacillus ferrooxidans, a micro-organism that can tolerate very high concentrations of heavy metals in its normal environment, normally accumulates high amounts of polyP granules and that the levels of intracellular polyP are greatly decreased when the bacterium is grown in or shifted to 100 mM Cu 2+ . In the presence of this metal, PPX activity and P i efflux greatly increased, supporting a model for metal tolerance mediated through polyP (Alvarez & Jerez, 2004).…”
Section: Introductionmentioning
confidence: 81%
“…Radioactively labelled polyP with a chain length of 750 residues was prepared as described by Ault-Riché et al (1998), with the modifications of Cardona et al (2001) and Alvarez & Jerez (2004). The identity and purity of [ 33 P]polyP 750 were determined by its susceptibility to hydrolysis by ScPPX1 as described previously (Ault-Riché et al, 1998;Cardona et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, much research has been focused on acquiring excellent bioleaching strains that have good traits and a higher copper resistance. Some copper-resistant strains have been obtained (Alvarez and Jerez, 2004); however, little is known about the mechanisms involved in copper resistance. The results of research conducted by Chisholm et al (1998) and Ahmad et al (2002) suggest that the copper-resistance genes of At.ferrooxidans are chromosomal and not plasmid based, but the role of these genes is still not clear.…”
mentioning
confidence: 99%